Effects of Ascorbic Acids on Post-Harvest Longevity of Chrysantemum Cut Flowers - Kurniawan Budiarto (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2019)
The longer vase life of chrysanthemum cut flower is one of the preferable quality traits in marketing for growers, retailers and consumers.  Several compounds, like ascorbic acid, have been reported to be able to prolong the post-harvest quality and longevity of cut flowers. Thus, the purpose of the study was to assess the ascorbic acid effects in several concentrations (0, 100, 200, and 300 ppm) in extending the fresh life of two chrysanthemum cultivars, i.e. cv. Remix (spray) and Yellow Fiji (standard).  The results showed that the termination of flower freshness was visually characterized by wilting of leaves and florets and the change in floret color (paler).  The supplementation of ascorbic acid solution at the concentrations of 200 and 300 ppm prevented and lengthened leaves and florets turgidity and postponed the wilting up to 2 – 3 days compared to control.  At the same concentrations, the solution also slowed down the degradation rates of chlorophyll content on leaves during vase life periods.